Analytical characterization of movements of the spinal column and risk assessment due to repeated movements of the upper limbs of building painters. Issue 3 (2nd July 2016) - Antonucci, Andrea; Forcella, Laura; Bonfiglioli, Roberta; Boscolo, Paolo; Violante, Francesco Saverio
Abstract : Manual activities of construction workers may induce musculoskeletal disorders. This study on a group of painters aimed to analytically characterize movements of the spinal column by both lumbar motion monitor and television cameras and to determine, using the Occupational Repetitive Actions (OCRA) Index method, the risk exerted by repeated movements of the upper limbs. The main results are: painting with a roller generally exposes workers to a lesser risk for upper limbs than painting with a brush; a roller-stick fixed at the wrong length can lead to stretching of the back at lumbar and cervical levels; to remain within the range of 'acceptable risk' (OCRA Index evaluation), a worker should not paint a vertical wall for over 3 h if using a roller and 2.5 h if painting with a brush; and, on average, a painter who paints for 5 h in a day lifts the bucket about 120, 140 times.